PREFERENCES OF RENT GARAGE OWNERS IN LOCATION SELECTION IN DALUNG VILLAGE, BADUNG REGENCY - Suryadinata, I Gusti Ngurah Eddy; Widiastuti, Widiastuti; Agusintadewi, Ni Ketut (ASTONJADRO, 2022)
Dalung Village, a residential development area in North Kuta District, Badung Regency, has many densely populated residential areas, yet the areas are not supported by adequate parking facilities. It is then used by the community around the residential areas to develop a rental garage business resulting in the direction of land use in Dalung Village in the current settlement designation area developing towards trade and services. This study aimed to determining the factors that become rental garage owner's preferences in choosing the location of a rental garage related to the characteristics of land use in Dalung Village. The research method used was a qualitative method with a case study approach. Data was collected through field observations, interviews and distribution of google form questionnaires to rental garage owner's. The results of this study indicate that the community's preference were the factor of the residential environment with lots of parking on the shoulders, the density factor of the number of vehicles that passed on public roads and environmental roads, environmental safety factors, capital and maintenance efficiency factors as well as the presence of similar businesses (rental garage) in an residential areas. The factor that made land use occurred was the lack of firmness of the Dalung village government and Badung district government in make arrangement for regional spatial planning areas and providing sanctions for violations of village spatial planning.